Chiral topologies for composite morphing structures – Part I: Development of a chiral rib for deformable airfoils (Phys. Status Solidi B 7/2015). Issue 7 (July 2015) - Airoldi, Alessandro; Bettini, Paolo; Panichelli, Paolo; Oktem, Mehmet F.; Sala, Giuseppe
<x xml:space="preserve">Abstract</x> Auxetic chiral topologies can be applied to design composite aeronautical morphing structures with the capability of progressive shape variations. Progresses towards the development of such composite chiral structures require fulfillment of aeroelastic constraints, adequate strength properties and feasible technological routes. Moving from a configuration identified by aeroelastic optimization, design methods and technological processes are set up and applied by Airoldi et al. (pp. 1435–1445) to accomplish such goals. The figure shows a chiral wing‐box demonstrator designed according to the chiral sail concept, which can lead to improve the stabilization effect of aerodynamic surfaces. Laminates made of carbon‐fibre reinforced plastic layers are produced. They are assembled by exploiting elastomeric tooling techniques and, finally, a chiral composite rib is manufactured and tested. In the background, a finite element study is shown for the production of chiral composite networks with enhanced strength properties, by using a simplified technological approach. The relevant numerical and experimental results are reported by Airoldi et al. on pp. 1446–1455.